Quality of Effective Microorganisms-based Liquid Fertilizer from Fermented Papaya Fruits (Carica papaya L.) - Simarmata, Wilander; Yurnaliza, Yurnaliza; Nurwahyuni, Isnaini (Universitas Labuhanbatu, 2022)
Papaya (Carica papaya L.) is one of the most popular fruits in the community and is generally only used as an ingredient for consumption in a fresh state. Papaya fruit production tends to be dynamic where sometimes the abundant amount of fruit may not necessarily be marketed directly. This causes the stock of papaya fruit during storage to rot and cannot be reused. This study aims to explore the potential of ripe papaya fruit to be processed as a substrate for the manufacture of liquid fertilizer using local microorganisms or effective microorganisms (EM). The quality of EM-based liquid fertilizer was determined based on the bacterial population density (CFU/mL) using the standard plate count (SPC) method on different growth media, then the levels of IAA and NPK in the applied fermented papaya fruit. The results showed the occurrence of nitrogen fixing bacteria, phosphate solubilizing bacteria and chitinolytic bacteria besides the cosmopolite bacteria. The optimum level of IAA in the fermented papaya fruit was EM + molasses (100%) while the NPK profile was still higher in the EM treatment without molasses.